Neutrophil extracellular traps induce endothelial dysfunction in systemic lupus erythematosus through the activation of matrix metalloproteinase-2. Issue 7 (25th February 2014) - Carmona-Rivera, Carmelo; Zhao, Wenpu; Yalavarthi, Srilakshmi; Kaplan, Mariana J
Abstract : Rationale: The structural and functional integrity of the endothelium is crucial in maintaining vascular homeostasis and preventing atherosclerosis. Patients with systemic lupus erythematosus (SLE) have an increased risk of developing endothelial dysfunction and premature cardiovascular disease. Neutrophil extracellular trap (NET) formation is increased in SLE and has been proposed to contribute to endothelial damage, but the mechanism remains unclear. Objective: To determine the mechanism by which enhanced NET formation by low-density granulocytes (LDGs) in SLE contributes to endothelial damage and disrupts the endothelium. Results: The putative role of NET-externalised matrix metalloproteinases (MMPs) in altering the functional integrity of the endothelium was examined. MMP-9 externalised by lupus LDGs during NET formation specifically impaired murine aortic endothelium-dependent vasorelaxation and induced endothelial cell apoptosis. Endothelial dysfunction correlated with the activation of endothelial MMP-2 by MMP-9 present in NETs, while inhibition of MMP-2 activation restored endothelium-dependent function and decreased NET-induced vascular cytotoxicity. Moreover, immunogenic complexes composed of MMP-9 and anti-MMP-9 were identified in SLE sera. These complexes, as well as anti-MMP-9 autoantibodies, induced NETosis and enhanced MMP-9 activity. Conclusions: These observations implicate activation of endothelial MMP-2 by MMP-9 contained in NETs as an important player in endothelial dysfunction, and MMP-9 as a novel self-antigen in SLE. These results further support that aberrant NET formation plays pathogenic roles in SLE.